ERGONOMIC AND PERSONAL PROTECTION EQUIPMENT (PPE) IMPLEMENTATION IN PT MACANAN JAYA CEMERLANG - Fikri Alkndi (Kreator, 2019)
Occupational Health and SafetyÂ  is one of the important factors in supporting the smooth production process. Therefore all workers and other people who are in the workplace must understand and actively participate in all activities that have an insight into occupational safety and health at PT. Macanan Jaya Cemerlang, and must always use Personal Protective Equipment (PPE) while in the company environment. Ergonomics and K3 are two inseparable things, both of which lead to the same goal of improving the quality of life of workers. Ergonomics is a science and its application that seeks to harmonize work and the environment for people or vice versa with the aim of achieving the highest productivity and efficiency through optimal human use. PT. Macanan Jaya Cemerlang as one of the major graphic companies in Indonesia, needs to implement good work ergonomics, to maintain employee productivity and work efficiency, and to improve physical and mental well-being through efforts to prevent injuries and occupational diseases (PAK). This thesis aims to determine whether the application of work ergonomics is related to safety and health in PT. Macanan Jaya Cemerlang whether it has been implemented properly.Keywords: OHS, Ergonomy and Printing Industry